The future of multicultural Britain : confronting the progressive dilemma - Pathak, Pathik (Edinburgh University Press, 2008)
Global politics are deeply affected by issues surrounding cultural identity. Profound cultural diversity has made national majorities increasingly anxious and democratic governments are under pressure to address those anxieties. Multiculturalism - once heralded as the insignia of a tolerant society - is now blamed for encouraging segregation and harbouring extremism. Pathik Pathak makes a convincing case for a new progressive politics that confronts these concerns. Drawing on fascinating comparisons between Britain and India, he shows how the global Left has been hamstrung by a compulsion for insular identity politics and a stubborn attachment to cultural indifference. He argues that to combat this, cultural identity must be placed at the centre of the political system. Written in a lively style, this book will engage anyone with an interest in the future of our multicultural society. Key Features Takes Britain and India as comparative case studies of two multicultural democracies Surveys new directions for the progressive Left following the demise of multiculturalism Challenges what the progressive position on cultural identity should entail